IJTIHAD DAN PROBLEMATIKA KEKINIAN - Muhammad Ruslan (Universitas Islam Lamongan, 2019)
The study of Islamic law and various global challenges requires a solutive method of ijtihad to solve contemporary issues today. In addition, social dynamics relating to the development of information technology and the spread of culture are in need of ijitihad in Islamic law. Yusuf Al-Qardawi has done a lot of contemporary ijithad as stated in this paper and how it could be addressed by Muslims in any part of the world, including Indonesia. The double movement theory of Fazlul Rahman has also taken part in giving an offer as a renewal of Islamic law over contextual legal issues without denying the basis of the primary sources of Islamic law, namely the Qur'an and Sunnah. The ijtihad method takes place through the historical criticism of norms at primary sources based on space and time and socio-cultural background. All this aims to capture the universality of the holy message contained in the primary sources. The value of universality is in the form of humanity, freedom (al-hurriyah), justice (al-adalah), and equality (al-musawah). This is relevant in the context of contemporary space and time especially in keeping up with the information industry era. This paper asserts the flexibility of the law based on sharia to provide solutions to the any emerging problems. Therefore, the teaching of legal methodology not only teaches the so-called ushul al-fiqh but also teaches the concepts that are relevant to the current social political situation and conditions.